MSME business tranformation through mobile e-commerce applications - Fajri, Muhammad Iqbal; Gani, Imam Prawiranegara; Fauzi, Fauzi; Manafe, Mesri Welhelmina Nisriani; Asmara, Maisa Azizah (Jurnal Info Sains : Informatika dan Sains, 2024)
The expansion of information technology fundamentally alters business operations and social interactions. For MSMEs, e-commerce is emerging as a significant force in digital marketing. Skills deficiencies in technology and restricted market access are obstacles. Mobile e-commerce application adoption offers substantial advantages, including access to international markets, enhanced operational effectiveness, and increased consumer involvement. Adoption of these applications increases the sales and operational efficacy of MSMEs, according to research. For MSMEs, the adoption of mobile e-commerce creates economic expansion and business opportunities. In order to create mobile e-commerce applications that are adaptable to market shifts and user demands, R&D is utilized. The primary functionalities of the application implementation outcomes are as follows user registration, order management, login, item data management, sales, payments, and transaction reports. The application is designed using the UML methodology, which depicts purchasers and system administrators as well as actions that can be executed based on feature requirements.